Linking Lean Hospitals and Management Control Systems:A ‎Systematic Literature Review on Efficiency, DigitalTransformation and Sustainability - Ambarriani, Anastasia Susty; Pradana, Bartolomeus Galih Visnhu (International Journal of Accounting and Economics Studies, 2026)
Lean hospital practices have gained increasing attention as healthcare systems face pressure to enhance efficiency, patient safety, and financial sustainability under bundled payment schemes such as iDRG/JKN. While lean management reduces waste and improves service ‎delivery, its effectiveness depends on robust Management Control Systems (MCS) to ensure alignment with organizational goals. This study systematically reviews the literature to examine the intersection of lean hospitals and MCS. Using the Scopus database, 114 peer-reviewed articles published between 2008 and 2025 were selected. Bibliometric and content analyses were conducted, supported by ‎VOSviewer and R Studio, to identify research trends, thematic clusters, and knowledge gaps. The findings reveal four dominant clusters: (1) ‎process-oriented lean practices, (2) organizational efficiency and performance, (3) integration with Industry 4.0 and sustainability, and (4) ‎quality improvement and benchmarking. The results indicate a clear shift from operational process improvement toward broader strategic ‎agendas involving digital transformation and sustainability. This review highlights research gaps in integrating lean hospitals with strategic MCS tools (e.g., balanced scorecard, activity-based management), the adoption of digital technologies (IoT, AI, digital twins), and ‎sustainability-driven frameworks (green lean). The study contributes by framing lean hospitals not merely as operational toolkits, but as strategic frameworks for smart and sustainable healthcare transformation, offering new insights for both scholars and practitioners.
Keywords: Lean Hospital; Management Control Systems; Systematic Literature Review; Efficiency; Digitalization; Sustainability